Financialisation, distribution, growth and crises: Long-run tendencies - Eckhard Hein; Nina Dodig (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
In this paper we review the empirical and theoretical literature on the effects of changes in the relationship between the financial sector and the non-financial sectors of the economy associated with 'financialisation' on distribution, growth, instability and crises. We take a macroeconomic perspective and examine four channels of transmission of financialisation to the macroeconomy: first, the effect on income distribution, second, the effects on investment in capital stock, third, the effects on household debt and consumption, and fourth, the effects on net exports and current account balances. For each of these channels we briefly review some empirical and econometric literature supporting the presumed channels, some theoretical and modelling literature examining the macroeconomic effects via these channels, and finally, we present small models generating the most important macroeconomic effects. We show that, against the background of redistribution of income at the expense of the labour income share and depressed investment in capital stock, each a major feature of financialisation, short- to medium-run dynamic 'profits without investment' regimes may emerge, which can be driven by flourishing consumption demand or by rising export surpluses, compensating for low or falling investment in capital stock. However, each type of these regimes, the 'debt-led consumption boom' type and the 'export-led mercantilist' type, contains internal contradictions, with respect to household debt in the first regime and with respect to foreign debt of the counterpart current account deficit countries in the second regime, which finally undermine the sustainability of these regimes and lead to financial and economic crises.
Keywords: E12; E22; E24; E44; F41; G01; 330; financialisation; distribution; growth; instability; financial and economic crisis; Kaleckian models; current account imbalances